Poligami dalam Perspektif Kitab Al-Amsal fi Tafsir Kitab Allah Al-Munazzal - Imron Rosyidi Muhammad (UIN Raden Mas Said Surakarta, 2017)
This article talks about polygamy in the perspective of â€œal-Amsal fi Tafsir Kitab Allah al-Munazzalâ€, the Quranâ€™s commentary wich written by NÄá¹£ir MakÄrim al-SyÄ«rÄzÄ«. This article is kind of libraryâ€™s research. By employing gender theory and discriptical analysis method, this article aims to explore the various concept of polygamy in Islam. As the result of this research, â€œal-Amá¹¡al FÄ« TafsÄ«r KitÄb Allah Al-Munazzalâ€ explained that polygamy was been known and practically committed by many nations in many places for a long time ago. This commentary book also explains the revelationâ€™s occasion of polygamy with the general description. NÄá¹£ir MakÄrim al-SyÄ«rÄzÄ« in this commentary book believes that Islam allows a man to commit the polygamy in requisite he had to treat all his wives fairly as possible. According to this commentary book, Polygamy in Islam is not just about the relation men and their wives, but also firmly related with the social aspect, that means, in some conditions, polygamy will be needed to be committed by the society. Despite in such points of its view of polygamy, this commentary book shows the gender justness, but in other points, this commentary book is seemingly showing the biased gender instead.